2019
DOI: 10.3390/genes10120980
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Divergence of a Novel DUF668 Gene Family in Rice Based on Comprehensive Expression Patterns

Abstract: The domain of unknown function (DUF) superfamily encodes proteins of unknown functions in plants. Among them, DUF668 family members in plants possess a 29 amino-acid conserved domain, and this family has not been described previously. Here, we report this plant-specific novel DUF668 gene family containing 12 OsDUF668 genes in rice (Oryza sativa) and 91 DUF668s for the other seven plant species. In our study, DUF668 genes were present in both dicot and monocot plants, indicating that DUF668 is a conserved gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…4). Moreover, the number of genes from the two broad groups was basically the same in rice and some Poaceae [2]. Surprisingly, we found that in addition to GhDUF668-06 and GhDUF668-06, the DUF668 gene family contains not only the DUF668 domain but also the DUF3475 domain in G. arboreum, G. raimondii and G. hirsutum.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…4). Moreover, the number of genes from the two broad groups was basically the same in rice and some Poaceae [2]. Surprisingly, we found that in addition to GhDUF668-06 and GhDUF668-06, the DUF668 gene family contains not only the DUF668 domain but also the DUF3475 domain in G. arboreum, G. raimondii and G. hirsutum.…”
Section: Discussionmentioning
confidence: 73%
“…A previous study indicated that more DUF668 family genes exist in cotton than in monocot and dicot plants [2]. This might contribute to the double duplication of the cotton genome, or it might be that more genes were annotated in cotton than in other species [30,31,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the hub genes, Podel.19G001200, which encodes a protein with a membrane attack complex component/perforin (MACPF) domain [50], and Podel.03G153500, which probable encodes a serine/threonine-protein kinase with a development and cell death (DCD) domain [51], are involved in cell development and programmed cell death. The domain of unknown function 668 (DUF668)-containing protein (Podel.02G021400) [52], the GRAM (from glucosyltransferases, Rab-like GTPase activators and myotubularins) domain-containing protein (Podel.06G003100) [53], and UDP-glycosyltransferases (Podel.04G076900) [54] are essential for plant defense against abiotic stress. The genes mentioned above might play an important role in the response to low N stress.…”
Section: Differences In Transcriptional Responses To Low N Stress Andmentioning
confidence: 99%